Components Affecting Intention to Use Online Dating Apps in India: A Study Conducted on Smartphone Users. (September 2019) - Chakraborty, Debarun
Online dating apps have a potential market throughout the world. India is also trying to capture this particular market through various apps like Tinder, Woo, TrulyMadly and so on. The different literatures have been analysed from various sources to find out the factors influencing the use online dating apps. This particular study has identified few key elements, which is motivating the online dating app users in India. A total of 296 samples have been selected from college goers and young professionals with the help of structured questionnaire. Simple random sampling has been used to conduct the study, and from all the metro cities, the responses have been collected. The multiple regression analysis has been used to find out the impact of factors towards utilising dating apps. Playfulness is the most impactful factor when compared to others. The study has also found that trust does not have any impact towards utilising dating apps. The study also implies that consumers mainly enjoy the dating apps, and they have very less trustworthiness towards these apps. The study is unique in nature as very few studies till date have been conducted in India.